2010
DOI: 10.1073/pnas.1004440107
|View full text |Cite
|
Sign up to set email alerts
|

Anthropocentrism is not the first step in children’s reasoning about the natural world

Abstract: What is the relation between human and nonhuman animals? As adults, we construe this relation flexibly, depending in part on the situation at hand. From a biological perspective, we acknowledge the status of humans as one species among many (as in Western science), but at the same time may adopt other perspectives, including an anthropocentric perspective in which human characteristics are attributed to nonhuman animals (as in fables and popular media). How do these perspectives develop? The predominant view i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
96
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 28 publications
8
96
0
2
Order By: Relevance
“…Researchers generally agree that children's concept of nature may not be universal and that several factors account for its variability. Age, language, culture, gender, place of residence and time spent in outdoor settings have been highlighted as significant influences on children's conceptualization of nature (Anggoro, Waxman, and Medin 2008, Atran et al 2001, Herrmann et al 2010, Unsworth et al 2012. Interestingly, how close a child feels to the natural world seems to account for variability in the concept of nature (Inagaki andHatano 2002, Medin et al 2010).…”
Section: Children's Concept Of Naturementioning
confidence: 99%
See 1 more Smart Citation
“…Researchers generally agree that children's concept of nature may not be universal and that several factors account for its variability. Age, language, culture, gender, place of residence and time spent in outdoor settings have been highlighted as significant influences on children's conceptualization of nature (Anggoro, Waxman, and Medin 2008, Atran et al 2001, Herrmann et al 2010, Unsworth et al 2012. Interestingly, how close a child feels to the natural world seems to account for variability in the concept of nature (Inagaki andHatano 2002, Medin et al 2010).…”
Section: Children's Concept Of Naturementioning
confidence: 99%
“…These include assessing children's moral reasoning about different environmental problems (Kahn, 1999) or evaluating whether children think of humans as similar to other living beings (mainly animals) (Carey 1985, Herrmann, Waxman, and Medin 2010, Levin and Unsworth 2013. Researchers generally agree that children's concept of nature may not be universal and that several factors account for its variability.…”
Section: Children's Concept Of Naturementioning
confidence: 99%
“…It involves extending one's biological knowledge to other living and non-living things, based on their perceived similarity to humans. For example, one would be more likely to attribute a heart or the ability to think to a lion than to an ant, because a lion is seen as being more similar to a human than an ant is (Carey, 1985;Coley et al, 2017;Hermann, Waxman, & Medin, 2010;Inagaki, 1990;Inagaki & Hatano, 1991;Inagaki & Sugiyama, 1988;Ross, Medin, Coley, & Atran, 2003). Anthropocentric thinking has not been as widely studied as teleological or essentialist thinking, and there are conflicting theories as to its developmental trajectory and role in intuitive biological thought.…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that "culturally-held belief systems within the community appear to influence children's reasoning about biological phenomena" (p. 9). Likewise, Hermann et al (2010) modified Carey's (1985 induction task to test children as young as three, and found that those 3-year-olds showed no preferential bias toward humans as an inferential base, suggesting a striking lack of anthropocentric thought as compared to their 5-year-old counterparts. These findings, taken together, suggest that anthropocentrism may not be a developmentally persistent cognitive default, but rather may be a culturally influenced cognitive strategy acquired later in development.…”
Section: Introductionmentioning
confidence: 99%
“…When asked whether a pig has the same kinds of insides as a cow or a piggy bank, for example, 3-y-olds are more likely to select the cow (3). Similarly, when told that dogs have "andro" inside, 3-y-olds are more likely to project this novel property to other animals (including mammals and nonmammals) than to artifacts (11).…”
mentioning
confidence: 99%